2010
DOI: 10.1086/653707
|View full text |Cite
|
Sign up to set email alerts
|

Increased Regulatory T Cell Counts in HIV‐Infected Nonresponders to Hepatitis B Virus Vaccine

Abstract: Hepatitis B virus (HBV) coinfection is a main cause of liver-related mortality in human immunodeficiency virus (HIV)-infected subjects. Unfortunately, HIV-infected subjects show a low rate of response to standard HBV vaccination (23%-56%), in contrast to rates >90% found in the general population, and the underlying causes (particularly cellular and molecular causes) are still unknown. We hypothesized that an increased frequency of regulatory T (T(reg)) cells could be involved in the low rate of seroconversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 37 publications
0
29
2
Order By: Relevance
“…A study by Whittall et al [32] demonstrated that the addition of CD40L and IL-4 in vitro were most effective in converting the immunologic signatures of non-controllers to those observed in HIC. Regulatory T-cells (T regs ) also play an important role in modulating immune responses and HBV vaccine response was found to be associated with lower baseline T reg frequency in HIV-infected persons [33]. Individuals with VL suppression, either naturally like HIC or by HAART, have lower levels of T regs compared with untreated persons with HIV [34].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Whittall et al [32] demonstrated that the addition of CD40L and IL-4 in vitro were most effective in converting the immunologic signatures of non-controllers to those observed in HIC. Regulatory T-cells (T regs ) also play an important role in modulating immune responses and HBV vaccine response was found to be associated with lower baseline T reg frequency in HIV-infected persons [33]. Individuals with VL suppression, either naturally like HIC or by HAART, have lower levels of T regs compared with untreated persons with HIV [34].…”
Section: Discussionmentioning
confidence: 99%
“…61 The number of T regulatory cells is often higher in individuals with HIV than in healthy donors, 62 and is independently associated with non-responsiveness to hepatitis B vaccine in individuals with HIV. 63 T regulatory cells inhibit B cell proliferation by directly inducing apoptosis of proliferating B cells. 64 …”
Section: Correlates Of Protection and Duration Of Protectionmentioning
confidence: 99%
“…Scarce data support this hypothesis, as increased numbers of regulatory T cells (CD4 + CD25 + FoxP3 + ) were demonstrated in the blood of NR after normal hepatitis B vaccination, compared to high-responders, 27 and in hepatitis B vaccine non-responsive HIV-infected subjects. 28 Whether these regulatory T cells are HBsAg specific remains to be investigated.…”
Section: Who Are Hepatitis B Vaccination Non-responders?mentioning
confidence: 99%